Determination of Escherichia coli in urine using a low-cost foil-based microfluidic device - Mašková, Tereza; Hárendarčíková, Lenka; Petr, Jan (Talanta, 2017)
We developed a simple low-cost cultivation-based microfluidic device from office-laminator foil and Parafilm for the determination of specific microorganisms in water samples. The main goal was to obtain a device that would be portable and cheap compared to common laboratory techniques testing microorganisms. This device needs only 10µL of a sample and can be easily used in terrain by a non-specialist. Moreover, we dealt with some technical aspects of the device fabrication such as low-cost lamination techniques and the use of different cultivation media.
Keywords: Urine; Cultivation; Low-cost microfluidics; moč; Escherichia coli; Lab-On-A-Chip Devices; laboratoř na čipu; Urinalysis; Humans; analýza moči; Lamination; Costs and Cost Analysis; lidé; náklady a analýza nákladů